Seven new records of bee flies (Bombyliidae, Diptera) from Saudi Arabia - Magdi El-Hawagry; Areej A. Al-Khalaf; Ahmed M. Soliman; Mahmoud S. Abdel-Dayem; Hathal M. Al Dhafer (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background Bombyliidae (bee flies) are one of the largest dipterous families in Saudi Arabia with 116 hitherto recorded species. Larvae of these flies are predators or parasitoids of different stages of other insects in the orders Orthoptera, Neuroptera, Coleoptera, Lepidoptera, Hymenoptera and Diptera, in addition to spiders (order Araneae, class Arachnida), so they have potential use as biological control agents for pests belonging to these orders. Results In the present study, the list of Saudi Arabian fauna of bee flies (family Bombyliidae) is supplemented with seven new records in five genera and four subfamilies. The newly recorded species are Parageron lutescens (Bezzi, 1925) [Usiinae], Phthiria salmayensis Efflatoun, 1945 [Phthiriinae], Heterotropus bisglaucus Bezzi, 1925, Heterotropus maculiventris Bezzi, 1925, Heterotropus xanthothorax Efflatoun, 1945 [Heterotropinae], Anthrax greatheadi El-Hawagry, 1999, and Desmatoneura brevipennis (Bezzi, 1924) [Anthracinae]. World and local distributions of recorded species, diagnoses, remarks on feeding behaviors and some colored photographs were provided. Conclusion The present study supplements the bee fly fauna (family Bombyliidae) in Saudi Arabia with seven new records. This brings the total number of bee fly species in the country into 123 species classified in 40 genera, 12 tribes and 10 subfamilies.